Nasopharyngeal Mucoepidermoid Carcinoma: A Rare Case Report - Mitat Arıcıgil; Mehmet Akif Eryılmaz; Hamdi Arbağ; Mehmet Dündar; Rukiye Özçelik Erdem (Genel Tıp Dergisi)
Introduction : Mucoepidermoid carcinoma is one of the common malignancies of the salivary glands. Nasopharyngeal mucoepidermoid carcinoma cases are rare. The treatment of these rare cases depends on the stage of the tumor and its invasion into the surrounding tissues. Case: A 63-year-old male patient, who was followed up for thyroid papillary carcinoma in 2006, was referred to our clinic after incidentally detected asymmetrical thickening of the nasopharynx on the left as a result of brain MRI during medical oncology follow-ups. The patient had a complaint of pain in the left neck region for about a month. Excisional biopsy from the lymph node that increased FDG uptake in the left jugulodigastric region in PET/CT and multiple punch biopsy from the nasopharynx were performed. The patient, whose pathology resulted in mucoepidermoid carcinoma, was referred to oncology to receive radiochemotherapy. Discussion: Although rare, it should be kept in mind that in patients presenting with a mass in the nasopharynx, mucoepidermoid carcinoma may be present. Although there is information about treatment options in the studies carried out to date, prospective studies are needed for prognosis and treatment selection.